2022
DOI: 10.3390/fermentation9010028
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Substrate on the Fermentation Characteristics and Culture-Dependent Microbial Composition of Water Kefir

Abstract: Water kefir is a sparkling fermented beverage produced by fermenting water kefir grains in a sucrose solution containing dried fruits or fruit extracts. The objective of this study was to investigate the influence of substrate composition on the fermentation kinetics and culture-dependent microbial composition of water kefir. First, the impact of different fruit substrates and nitrogen limitation was examined. Fermentation of different fruit-based media with a single water kefir culture demonstrated that the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…Regarding yeasts, we found a high abundance of P. membranifaciens, Pichia kudriavzevii, and K. exigua. This finding is interesting since some studies, which even change substrate conditions ( Laureys and de Vuyst, 2016 ; Zannini et al, 2023 ), have not detected P. membranifaciens nor K . exigua , denoting the uniqueness of this WK fermentation and its chemical space.…”
Section: Discussionmentioning
confidence: 79%
“…Regarding yeasts, we found a high abundance of P. membranifaciens, Pichia kudriavzevii, and K. exigua. This finding is interesting since some studies, which even change substrate conditions ( Laureys and de Vuyst, 2016 ; Zannini et al, 2023 ), have not detected P. membranifaciens nor K . exigua , denoting the uniqueness of this WK fermentation and its chemical space.…”
Section: Discussionmentioning
confidence: 79%
“…Water kefir fermentation promotes bacterial metabolism, resulting in acidification, that is, faster conversion of sucrose to its monosaccharides and lactic acid. MDK and PNK samples had acetic acid, whose esters are responsible for water kefir's fruity flavor and aroma; acetic acid was previously identified in water kefir (Randazzo et al, 2016 ; Zannini et al, 2022 ).…”
Section: Resultsmentioning
confidence: 89%
“…MDK and PNK samples had acetic acid, whose esters are responsible for water kefir's fruity flavor and aroma; acetic acid was previously identified in water kefir (Randazzo et al, 2016;Zannini et al, 2022).…”
Section: Organic Acid Contentsmentioning
confidence: 86%
“…In fact, some authors have already demonstrated that the properties of EPS synthesized from pure cultures may differ from those synthesized in cocultures in terms of composition, thermodynamic properties, and surface morphology [ 58 , 59 ]. This highlights the importance of microbial interactions in complex microbial consortia and how the pressure exerted by the growth substrate alters these interactions, ultimately affecting EPS synthesis [ 60 ].…”
Section: Resultsmentioning
confidence: 99%